Attitudes of secondary stage teachers in Quwaiy'yah Governorate in Saudi Arabia towards E-learning. - Naief A. Mutawa (Sultan Qaboos University, 2013)
This study aimed at investigating the attitudes of secondary school teachers in Quwaiy'yah Governorate towards e- learning. To achieve the aim of the study, a questionnaire was developed and administered after testing its validity and reliability. This questionnaire consisted of 24 items. Means and standard deviations were calculated and one-way ANOVA was used to answer the study questions. T- test was used to answer the third and fourth questions.The results of the study showed that there were no statistically significant differences in the participants' attitudes towards e-learning due to experience and specialization. However, attending training courses was found a significant factor that affect teachers' attitudes. Teachers who attended training courses showed more positive attitudes towards e-learning than teachers who did not attend training coursed. The study put forward some recommendations. An important implication is that teachers ought to attend training courses and workshops in e-learning.